Study of Mass and Energy Yields of an Agroforestry Residues Carbonizer - Nouhou, Doulla Seydou; Ali, Aboubacar; Ibrahim, Horouna Gado (Seventh Sense Research Group, 2021)
Energy recovery from processing wastes of agricultural products is a solution to their management issues and a means of energy production. In addition, it contributes to the reduction of deforestation. The objective of this study is to develop a method of agroforestry residues carbonization. The residues used to consist of the shell of the doum palm (hyphaenethebaica) and the rice husk. Carbonization is in partial combustion, and the device used is a metal furnace made up of three (3) stages. The peaks of temperatures, mass and energy yields, and the quality of the coal (fixed carbon rate) were determined at each stage of the carbonized. The mass yields obtained for stages 3, 2, and 1 are 66.41%, 42.60%, and 21.57% for the shell of the doum palm and 46.94%, 67.19% 24.83% for the rice husk. The energy yields are 82.41%, 57.05%, and 30.97% for the shell of the doum palm and 56.1%, 74.58%, and 26.66% for the rice husk. The coal quality (fixed carbon rate) for the same stages 3, 2, and 1 is 35.32%, 44.42%, and 52.32% for the shell of the doum palm and 32.55%, 30, 43%, and 30.75% for the rice husk. The cycle time is 9.03h for the shell of the doum palm against 11.22h for the rice husk. This study shows that the shell of the doum palm produces better quality charcoal compared to the rice husk and that the charcoal obtained at stage 1 ( ) can be used not only for gasification but also for direct home use.
International Journal of Engineering Trends and Technology, Volume 69, Issue 11
Keywords: Rice husk; Coal/Charcoal; Carbonization/charring; Hull/Shell of doum palm; Makinta Boukar; Université Abdou Moumouni; Education